Peran Pendidikan Kebudayaan dalam Pelestarian Kearifan Lokal di Sekolah : Tinjauan Pustaka - Siti Mahrani Batubara (Universitas Palangka Raya, 2025)
Cultural education is crucial for preserving local wisdom, especially in Indonesia, which is rich in diverse traditions and cultures. However, there are many challenges in maintaining it, particularly in the era of modernization and technological advancement. One way to preserve local wisdom is through education. Education, in general, plays a role in civilization, where the goal of civilization is to improve the quality of humanity, ultimately producing advanced and civilized individuals. Values, knowledge, and cultural practices that have been passed down through generations are known as local wisdom. The aim of this article is to examine how cultural education can help maintain, preserve, and transmit local wisdom to younger generations. Cultural education can enhance appreciation and love for local culture, as well as foster an understanding of local history and identity. A context-based approach allows cultural education to link academic knowledge with everyday life. It can also strengthen public awareness of the importance of preserving traditions. In the face of globalization challenges, cultural education is also vital in raising the awareness of younger generations to differentiate external influences without disregarding indigenous culture. By integrating the values embedded in local wisdom into the school curriculum and promoting education based on local wisdom practices, education can play a key role in preserving local wisdom. Therefore, integrating cultural education into both formal and informal curricula is a strategic step to ensure the preservation of local wisdom in the modern era. Education based on local wisdom helps teachers, students, and schools preserve the potential of each region and generate learning that respects cultural diversity.